A comparison of physicians’ and other health care professionals’ perceived adoptions of smartphone - Park, Yangil; Putzer, Gavin J. (IJRDO - Journal of Business Management, 2016)
Portable devices such as the smartphone are transforming the healthcare industry. Our study explores the adoption behavior of health professionals in regional hospitals. This study employed a comparative design via questionnaire to investigate perception differences among 323 practitioners in US. Professionals were divided into four groups: physician, nurse, administrator, other professional. The results showed significant differences in several variables: attitude toward using a smartphone, observability, compatibility, personal demographics, and internal/ external environments. Adoption rates in large hospital settings approximated 70%; whereas, in smaller settings only 35%. The smartphone adoption in rural areas was less than metropolitan areas; yet, the advantages of using a smartphone for clinical tasks were well perceived. It appears a user’s perception is significantly different between the groups.